Frequency of Th17 cells correlates with the presence of lung lesions in pigs chronically infected with Actinobacillus pleuropneumoniae. (January 2018) - Sassu, Elena; Ladinig, Andrea; Talker, Stephanie; Stadler, Maria; Knecht, Christian; Stein, Heiko; Frömbling, Janna; Richter, Barbara; Spergser, Joachim; Ehling-Schulz, Monika; Graage, Robert; Hennig-Pauka, Isabel; et al.
Abstract Porcine contagious pleuropneumonia caused byActinobacillus pleuropneumoniae (APP) remains one of the major causes of poor growth performance and respiratory disease in pig herds. While the role of antibodies against APP has been intensely studied, the porcine T cell response remains poorly characterized. To address this, pigs were intranasally infected with APP serotype 2 and euthanized during the acute phase [6–10 days post-infection (dpi)] or the chronic phase of APP infection (27–31 dpi). Lymphocytes isolated from blood, tonsils, lung tissue and tracheobronchial lymph nodes were analyzed by intracellular cytokine staining (ICS) for IL-17A, IL-10 and TNF-α production after in vitro stimulation with crude capsular extract (CCE) of the APP inoculation strain. This was combined with cell surface staining for the expression of CD4, CD8α and TCR-γδ. Clinical records, microbiological investigations and pathological findings confirmed the induction of a subclinical APP infection. ICS-assays revealed the presence of APP-CCE specific CD4+ CD8αdim IL-17A-producing T cells in blood and lung tissue in most infected animals during the acute and chronic phase of infection and a minor fraction of these cells co-produced TNF-α. APP-CCE specific IL-17A-producing γδ T cells could not be found and APP-CCE specific IL-10-producing CD4+ T cells were present in various organs but only in a few infected animals. The frequency of identified putative Th17 cells (CD4+ CD8αdim IL-17A+ ) in lung and blood correlated positively with lung lesion scores and APP-specific antibody titers during the chronic phase. These results suggest a potential role of Th17 cells in the immune pathogenesis of APP infection.